Evaluation of antimicrobial activity of thiolated methylated N‐(4‐N, N‐dimethylaminobenzyl) chitosan as a new derivative of chitosan. (1st December 2022) - Dehdari, S.; Rastegari, A.; Samadi, N.; Mohammadi, Z.
Abstract: Despite chitosan, a natural cationic polysaccharide derived from chitin, being applied as an antimicrobial agent, many studies are being performed for enhancing its capability to fight against pathogens. The aim of this study was to investigate the antibacterial effect of thiolated methylated N‐(4‐N, N‐dimethylaminobenzyl) chitosan (TTMAC) polymer and its nanoparticles as a novel derivation of chitosan. The polymer derivative was synthetized and characterized via 1 H NMR, Fourier transform infrared and the Elman test. The nanoparticles with different N/P ratios were prepared by the ionic gelation method and were characterized by dynamic light scattering and transmission electron microscopy. The cellular toxicity of polymer and nanoparticles at different concentrations were evaluated on human MCF‐7 cell line. Antimicrobial assay was performed on Escherichia coli (ATCC 25922), Staphylococcus aureus (ATCC 25923) and Candida albicans (ATCC 10231) as Gram‐negative, Gram‐positive and yeast pathogens, respectively. The obtained results have shown the TTMAC polymer has a higher inhibition activity against microbial pathogens and also lower cellular toxicity in comparison with chitosan polymer. Furthermore, chitosan nanoparticles in comparison with TTMAC nanoparticles have lower size and highest zeta potential in different ratio and chitosan nanoparticles have more inhibitory effects against microbial pathogens. In conclusion, TTMAC derivative in polymeric form can be a promising tool against microbial pathogens. Abstract: Significance and Impact of the Study: Bacterial infection is a major challenge in the world. Using membrane‐targeting cationic polymers make an efficient approach for fighting bacterial infection. In this study, thiolated, methylated N‐(4‐N, N‐dimethylaminobenzyl) chitosan polymer showed efficient antimicrobial effects against Gram‐positive and Gram‐negative bacteria and also against yeast.